A Summary of Florida's Law of Quarantine of Persons and Public Health Law Reform Issues - Ann L. Abbott (University of North Florida, 2005)
Laws related to quarantine of individuals have existed in the United States since the time of the American Revolution. Review, reform, and enforcement of these laws are essential as public health is asked to address new challenges (e.g., SARS) as well as traditional communicable diseases such as TB and various STDs. This article examines the basis for quarantine and reviews the health and legal circumstances for their enactment and enforcement. The relevance of various Florida statutes and regulations is demonstrated with respect to evolving public health considerations and a reform movement.